A propaedeutic to the taxonomy of the Eastern cottontail rabbit (Lagomorpha: Leporidae: Sylvilagus floridanus) from Central America - Ruedas, Luis A.; López, Lucía I.; Mora, José M. (THERYA, 2023)
To ascertain the taxonomic identity of cottontail rabbits from Costa Rica, we examined the holotypes of all the taxa of Sylvilagus currently subsumed within the Sylvilagus floridanus species complex as defined by Philip Hershkovitz. The almost 40 named taxa contained in S. floridanus are widespread from northeastern to north-central North America in the north (including southern Canada), through Central America to northwestern South America. Here, we examine Mesoamerican taxa in the complex, on the basis of holotypes, and test the hypothesis of conspecificity among them. Our examination of the holotypes, along with uni- and multivariate assessments of mensural variation as well as character variation in existing and newly acquired specimens from Costa Rica, indicate that S. floridanus (J. A. Allen, 1890) sensu stricto is restricted to North America, with its southern limit at the Isthmus of Tehuantepec. Sylvilagus yucatanicus (Miller, 1899) is limited to the Yucatan Peninsula. Sylvilagus hondurensis Goldman, 1932 is retained as a species, with S. h. costaricensis Harris, 1933 as a junior synonym. Costa Rica is revealed to have three described species: S. gabbi (J. A. Allen, 1877), S. hondurensis costaricensis, and S. dicei Harris, 1932. However, there are indications that this taxonomic scheme may in fact underrepresent the existing number of biological species of Sylvilagus present in that country.